Metabolomic Prediction of Naphthalene Pneumo-Toxicity in the Snail Helix aspersa maxima - Aude Devalckeneer; Marion Bouviez; Jean-Marie Colet (Metabolites, 2025)
Background: Polluted soils represent a major problem in many industrialized countries that urgently requires appropriate health risk assessment. The One Health concept that considers a close relationship between human and animal health and ecosystems relies, among other techniques, on continuous monitoring through the use of animal species as bioindicators. In this context, terrestrial gastropods, already recognized as relevant indicators due to their anatomo-physiology, provide a reliable model to study the pneumotoxic effects of pollutants. On the other hand, risk assessment is based on multi-biomarker studies. Therefore, omic approaches seem particularly useful since they can simultaneously detect numerous early biological changes. Methods: In this study, Helix aspersa maxima was exposed to naphthalene, a highly volatile aromatic hydrocarbon responsible for numerous respiratory disorders. Pulmonary membrane extracts and hemolymph samples were analyzed by 1H-NMR spectroscopy after single or repeated exposures to naphthalene. Results: Numerous metabolic changes were observed, which could be related to membrane lesions, energy, anti-inflammatory, and tumorigenesis pathways. Conclusions: Our findings highlight the potential of combining animal indicator and omics techniques to predict respiratory health risks in cases of exposure to polluted soils.